(3GdagOI GdLGeYI aj fXe GdYbjOI GdfGaYIs - (3UGdM Hf GdUOjb GdfeGRis; (3YHO GdQMef Hf CMeO Hf YHO GdZaGQ, CHh GdaVd, nYoVO GdOjf GdEjLj,J (B756 (3g` s ((3CMeO Hf jhSa ajQhR s)
(3ChdgG (B:s
(3bGd GdfeGRi GdabjQ UGdM CMeO QHi Gddg agh GdaGJM hgPg ceG JQi CQLhRI LGeYI hGVMI hLjRg fXeJ ajgG HYO GdESJNGQI YbjOI UMjMI eNJGQg s
(3BNQgG (B:s
(3Ke UdGI Gddg hGdSdGe eG EgJR ZUf ChTOhG MeGe Ydi GdfHi GdeUWai eMeO hidg Cgd GdJbi hGdSDOO s
(3Vef eLehY , JQJjHgG (B: (3ef U (B118 - (3U(B125s
(3GdfSNI HgG MhGTs
(3fSNI CNQis
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B66 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B119 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B527s
Keywords: (3GdJhMjO hGdedd hGdfMds